IMF Staff papers : Volume 28 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1981)
This paper surveys theoretical issues and empirical evidence on the effects of central bank intervention in foreign exchange markets on exchange rate movements. The focus is on the ability of fully sterilized intervention to influence exchange rates in a predictable manner. Theoretical considerations suggest that the exchange rate may be affected by intervention if assets denominated in different currencies are imperfect substitutes, thus creating opportunities for intervention (undertaken for portfolio balance reasons) to modify interest differentials and, hence, the exchange rate. The same conclusion emerges when one looks at the effects of intervention on risk premiums in the foreign exchange markets, on differences between offshore and domestic interest rates, and on covered international interest differentials. The lack of any firm evidence that portfolio balance effects resulting from intervention in foreign exchange markets affect exchange rates predictably suggests that intervention policy cannot be distinguished from general monetary policy for practical purposes. This, in turn, implies that attempts to use these two policy instruments independently may lead to lesser, rather than to greater, exchange rate stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet